Soft Hands, Hard Power: Sponging Off the Empire of Leisure (Virgil, Georgics 4). (15th April 2018) - Geue, Tom
Abstract: This article seeks to jumpstart the politico-historicist scholarship on Virgil's Georgics in the direction of Marxist criticism. I argue that the Georgics should be understood less as a battle site for intra-elite power struggles or civil strife, more as an ideological stomping ground to work out, and dig in, the particular relationships of slavery and imperialism disfiguring the Roman world in 29b.c.e . After a brief analysis of the dynamics of labor in Books 1–3, I train on a close reading of Book 4, which sees the bees ( et al .) as crucial to the new dominant logic of compelling others (whether slaves or provincial subjects) to produce and give up the fruits of their labour — all for the leisured enjoyment of the upper crust.